Investigation of TG-43 dosimetric parameters for 192Ir brachytherapy source using GATE Monte Carlo code - Musa Joya; Hassan Ali Nedaie; Ghazale Geraily; Hadi Rezaei; Awaz Bromand; Mahdi Ghorbani; Peyman Sheikhzadeh (Journal of Medical Physics, 2023)
Purpose: According to the revised Task Group number 43 recommendations, a brachytherapy source must be validated against a similar or identical source before its clinical application. The purpose of this investigation is to verify the dosimetric data of the high dose rate (HDR) BEBIG 192Ir source (Ir2.A85-2). Materials and Methods: The HDR 192Ir encapsulated seed was simulated and its main dosimetric data were calculated using Geant4 Application for Tomographic Emission (GATE) simulation code. Cubic cells were used for the calculation of dose rate constant and radial dose function while for anisotropy function ring cells were used. DoseActors were simulated and attached to the respective cells to obtain the required data. Results: The dose rate constant was obtained as 1.098 ± 0.003 cGy.h − 1.U − 1, differing by 1.0% from the reference value reported by Granero et al. Similarly, the calculated values for radial dose and anisotropy functions presented good agreement with the results obtained by Granero et al. Conclusion: The results of this study suggest that the GATE Monte Carlo code is a valid toolkit for benchmarking brachytherapy sources and can be used for brachytherapy simulation-based studies and verification of brachytherapy treatment planning systems.